Awareness and knowledge about bioterrorism among medical students at a University in Malaysia - Bikram Kabir,; Durgadas Govind Naik,; Venkata Pavan Kumar,; Geethanjali Bhas, (Malaysian Society of Applied Biology, 2016)
The use of biological agents as weapons in warfare has been practiced since antiquity and is on the rise recently. In the event of an act of bioterrorism, health care professionals have to be prepared to identify and counter such incidents. They have to recognize and initiate rapid response to acts of bioterrorism underlining the importance of awareness and preparedness for bioterrorism. A closed questionnaire based survey, conducted among medical students, to assess their awareness and knowledge on bioterrorism included questions on biosafety, biosecurity, target population, biological agents, role of doctors and hospitals, response and scope. Results were analyzed by using simple statistical applications. Of 132 respondents, 64% were aware of the term bioterrorism. Students were aware of important etiological agents used in bioterrorism; Bacillus anthracis (52%), Ebola virus (58%), Small pox (51%), Vibrio cholerae (41%) and Clostridium botulinum (28%). Majority of students were aware about the importance of identifying illness, and reporting to concerned health officials and 95% respondents opined that, inclusion of bioterrorism in curriculum provides scope for expansion of preparedness. This study indicates a need to include bioterrorism as a topic in curriculum, thereby providing basic knowledge and preparedness to respond to bioterrorism.